Pengaruh Konsentrasi Gula dan Daging Buah terhadap Mutu Serbuk Instan Jus Alpukat (Persea americana Mill) - Susanti, Afryani; Tamrin, Tamrin; Kuncoro, Sapto; Warji, Warji (Jurnal Agricultural Biosystem Engineering, 2022)
Indonesia is a tropical country rich in plant varieties. Plants thrive and produce is used to a food source, such as the avocado, which produces fruit that be consumed. One way to maintain the quality, quantity and continuity of horticultural products that must be maintained for a relatively long period of time is to use post-harvest technology assistance so that the condition of fruit and vegetables can be maintained and does not affect changes in prices and consumer demand. The aim of this study is to study the effect of sugar, water and avocado pulp concentrations on the quality of avocado juice powder. The results showed that the yield value was 48%, the avocado juice powder density was 0.65 g/mL. The organoleptic test, which was performed by color, had criteria close to the same, the aroma had criteria like that, the taste was closer to a little sweet. Keywords: Avocado, Post-Harvest Technology, Avocado Powder.